Upper and Lower almost $(τ_1,τ_2)$-continuous Multifunctions (European Journal of Pure and Applied Mathematics, 2024)
This paper is concerned with the concepts of upper and lower almost $(τ_1,τ_2)$-continuous multifunctions. Furthermore, some characterizations of upper and lower almost $(τ_1,τ_2)$-continuous multifunctions are investigated.
Keywords: upper almost $(τ_1,τ_2)$-continuous multifunction; lower almost $(τ_1,τ_2)$-continuous multifunction